KOMPOSISI FISIK KARKAS ITIK BALI YANG DIBERI RANSUM MENGANDUNG DAUN PEPAYA TERFERMENTASI - N. N. D., Arisandy; Siti, N. W.; Ardika, I N. (Jurnal Peternakan Tropika; Vol 5 No 1 (2017), 2017)
The study aimed was to find out the physical composition of bali ducks female carcasses given fermented papaya leafs in the ration has been held in Kediri, Tabanan, during 3 months.  Data obtained was analyzed using Randomized Completely Design (RCD) were treated with three treatments and five replications with 45 bali ducks female were used in this study.  The treated including is P0 (commercial ration as a control), P1 (commercial ration + 5% fermented papaya leafs) and P2 (commercial ration + 10% fermented papaya leafs). The variables observed were: the carcass weight, meat weight, skin including subcutaneous fat weight, bone weight, carcass percentage, meat percentage, bone percentage, and skin including subcutaneous fat percentage. The results showed that carcass weight and meat weight of bali ducks female in P1 treatment significantly (P<0.05) higher then P0 treatment, but the treatment of P2 non significantly (P>0.05) higher then P0 treatment and non significantly (P>0.05) lower then P1 treatment. Bone weight, skin including subcutaneous fat weight, bone percentage, and skin including subcutaneous fat percentage in P1 and P2 treatment non significantly (P>0.05) lower then P0 treatment, while carcass percentage and meat percentage in P1 and P2 treatment non significantly (P>0.05) higher then P0 treatment.
Keywords: physical composition carcass, bali duck, papaya leafs